2012
DOI: 10.1007/s00262-012-1256-y
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of Stat3-siRNA and endostatin combined therapies, delivered by attenuated Salmonella, on orthotopically implanted hepatocarcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most aggressive carcinomas. Limited therapeutic options, mainly due to a fragmented genetic understanding of HCC, and major HCC resistance to conventional chemotherapy are the key reasons for a poor prognosis. Thus, new effective treatments are urgent and gene therapy may be a novel option. Signal transducer and activator of transcription 3 (Stat3) is a highly studied member of the STAT family. Inhibition of Stat3 signaling has been found to suppress tumor growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…We found that combined application of nifuroxazide and TCL-loaded DC significantly inhibited the expression of p-STAT3 compared with PBS group and nifuroxazide group. Inhibition of the expression of STAT3 increased the T cell infiltration and proliferation (32). Moreover, application of nifuroxazide inhibited the proliferation of MDSC that had an immunosuppressive effect on antitumor responses (17).…”
Section: Discussionmentioning
confidence: 99%
“…We found that combined application of nifuroxazide and TCL-loaded DC significantly inhibited the expression of p-STAT3 compared with PBS group and nifuroxazide group. Inhibition of the expression of STAT3 increased the T cell infiltration and proliferation (32). Moreover, application of nifuroxazide inhibited the proliferation of MDSC that had an immunosuppressive effect on antitumor responses (17).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous experimental findings and those of other reports (Tian et al 2012; Pawelek et al 1997; Low et al 1999) show that attenuated S. typhimurium can specifically home to tumor cells, possibly via tumor-associated macrophages. The Endostatin and Si-Stat3 combination therapy also activates anti-tumor immune responses (Jia et al 2012). Interestingly, in the current study, combined treatment with Endostatin and siRNA specific to Stat3 also activated various immune cells and cytokines (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblotting was performed as previously described. 52 For immunoblotting, cell lysates were obtained after cell debris discarded. Proteins were separated in 12% SDS-PAGE gels, transferred to polyvinylidene difluoride (PVDF) membranes (Millipore Corp, Billerica, MA, USA) and immunoblotted with appropriate primary antibodies specific for total Stat3, p-Stat3, β -antin (Cell Signaling Technology, Danvers, MA, USA) or TLR-9 (Santa Cruz Biotechnology, Delaware Ave Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%